Inorganic micro- and nanomaterials : synthesis and characterization - Dibenedetto, Angela; Aresta, Michele, 1940- (Walter de Gruyter GmbH & Co. KG, 2013)
The demand for new materials with novel properties on the micro- and nano-scale continues to grow. This book provides an overview of state-of-the-art techniques for the synthesis and characterization of inorganic nanomaterials including techniques such as XPS, XAS, single crystal X-ray diffraction, X-ray microimaging, electron microscopy, and solid state NMR. Essential for all researchers in nanoscience.